Comparação de soluções para fundações superficiais de divisa em um sobrado - Haefliger, Robson Humberto Rossatto (My University, 2021)
The development of studies in construction area, in addition to seeking economically positive solutions, is also required by the reduction of materials consume, which production is considered aggressive for the environment. When building close to the land boundaries, is necessary to use special foundations that do not encroach the neighboring land, this being a very specific case that causes an increase in inputs and, consequently, in investment. That considerer, this work analyzes different solutions for boundary footing in the construction of a 150m² two-story house in Bento Gonçalves, Rio Grande do Sul, place that has soil that justifies the use of shallow foundations. Four options are analyzed with the help of the CYPECAD software: eccentric footing without balance beam, eccentric footing with balance beam, centered footing with transition beam and "T" shaped footing, being the results compared regarding: consumption and budgeting of steel, concrete and wood, and axial and bending effort. Finally, the "T" shaped footing solution is presented as the most economically advantageous, in addition to demonstrating that the methods that are most used in Brazil are also the least economical for this situation. [resumo fornecido pelo autor]
O desenvolvimento de estudos na área da construção civil, além de sempre buscar soluções economicamente favoráveis, é demandado também pela redução do consumo de materiais cuja a produção seja agressiva ao meio ambiente. Ao construir uma obra junto aos limites do terreno, é necessária a utilização de fundações especiais que não invadam o terreno vizinho, sendo esse um caso bem específico que ocasiona o aumento de insumos e, consequentemente, do investimento. Sendo assim, este trabalho analisa soluções distintas para sapatas de divisa na construção de um sobrado de 150 m² em Bento Gonçalves, Rio Grande do Sul, local que possui um solo que justifique a utilização de fundações superficiais. São analisadas quatro opções com o auxílio do software CYPECAD: sapata excêntrica sem travamento, sapata excêntrica com viga de equilíbrio, sapata centrada com viga de transição e sapata em formato "T", uma vez que se comparam os resultados referentes a: consumo e orçamentação do aço, concreto e madeira, e esforço axial e de flexão. Por fim, é apresentada a solução de sapata em formato "T" como a mais vantajosa economicamente, além de ser demonstrado que os métodos mais utilizados no Brasil são também os menos econômicos para esta situação. [resumo fornecido pelo autor]
Keywords: Engenharia civil; Fundações (Engenharia); Projeto estrutural; Concreto armado